Polyphasic characterization of antibiotic resistant and virulent Enterococci isolated from animal feed and stored-product insects - Channaiah, Lakshmikantha H. (Kansas State University, 2009)
Feed samples and live stored-product insects from feed mills and swine farms were collected and cultured for Enterococcus spp. The mean concentration of enterococci in insect and feed were 2.7 ± 0.5 × 101 cfu/insect and 6.3 ± 0.7 × 103 cfu/g respectively. A total of 362 isolates of enterococci collected from 89 feed samples and 228 stored-product insects were identified to the species level using PCR. These isolates were represented by Enterococcus casseliflavus (53.0%), E. gallinarum (20.4%), E. faecium (16.2%), E. hirae (5.2%), and E. faecalis (5.0%). Enterococci were phenotypically resistant to tetracycline (48.0%), erythromycin (14.3%), streptomycin (16.8%), kanamycin (12.1%), ciprofloxacin (11.0%), ampicillin (3.3%), and chloramphenicol (1.1%). All isolates were susceptible to vancomycin and gentamicin. Tetracycline resistance was encoded by tetM (50.0%), tetO (15.1%), tetK (0.5%), tetS (0.2%) and other unknown tetracycline determinants. Enterococci carried virulence genes including gelatinase (gelE; 21.5%), an enterococcus surface protein (esp; 1.9%), and cytolysin (cylA; 2.2%). An aggregation substance (asa1) gene was detected in 61.0% of E. faecalis isolates. Fifty perncet of E. faecalis isolates were phenotipically tested positive for aggregation substances. Enterococci with cylA genes were hemolytic (52.0%) and with gelE genes were gelatinolytic (18.5%). The ermB gene, encoding erythromycin resistance was detected in 8.8% of the total isolates. The Tn916/1545 family of conjugative transposons was detected in 10.7% of the isolates. Laboratory experiments showed that adults of the red flour beetle, Tribolium castaneum (Herbst), fed on poultry and cattle feeds inoculated with E. faecalis OG1RF:pCF10, were able to successfully acquire enterococci and contaminate sterile poultry and cattle feeds. To assess the potential of horizontal gene transfer, conjugation assays were carried out with E. faecalis using a donor (wild strains) and recipient (E. faecalis OG1SSP) in ratio of 1:10. Only one isolate (1 out of 18 E. faecalis) could transfer tetM to a recipient using broth mating. However, filter mating assay, followed by PCR confirmation revealed that 89.0% (16 out of 18 E. faecalis) of isolates could transfer tetM to E. faecalis. Transfer ratios of transconjugant per recipients ranged from 2.6 × 10-4 to 1 × 10-9. In summary, feed (52.0%) and stored-product insects (41.6%) collected from feed mills and swine farms carried antibiotic-resistant and potentially virulent enterococci. Our study showed that T. castaneum, a pest commonly associated with feed, served as a potential vector for enterococci in the feed environment. Conjugation assays followed by PCR confirmed presence of the tetM gene on a mobile genetic element(s) such as Tn916 and may be horizontally transferred to other Enterococcus species and to other bacteria of clinical significance.
Keywords: Enterococci; Antibiotic resistance; virulence; animal feed; stored-product insects; Agriculture, Food Science and Technology (0359); Biology, Microbiology (0410)